PAQR6 as a prognostic biomarker and potential therapeutic target in kidney renal clear cell carcinoma - Zou, Tao; Jia, Zongming; Wu, Jixiang; Liu, Xuxu; Deng, Minghao; Zhang, Xuefeng; Lin, Yuxin; Ping, Jigen (Frontiers in Immunology, 2024)
BackgroundProgestin And AdipoQ Receptor Family Member VI (PAQR6) plays a significant role in the non-genomic effects of rapid steroid responses and is abnormally expressed in various tumors. However, its biological function in kidney renal clear cell carcinoma (KIRC) and its potential as a therapeutic target remain underexplored.MethodsIn this study, PAQR6 was identified as a critical oncogene by WGCNA algorithm and differential gene expression analysis using TCGA - KIRC and GSE15641 data. The differences in PAQR6 expression and its association with KIRC survival outcomes were investigated, and transcriptomic data were used to further elucidate PAQR6’s biological functions. Moreover, XCELL and single - cell analysis assessed the correlation between PAQR6 expression and immune infiltration. TIDE algorithm was used to assess how well various patient cohorts responded to immune checkpoint therapy. Finally, the role of PAQR6 in the development of KIRC was verified through EdU, scratch assays, and Transwell assays.ResultsOur findings suggest that elevated expression of PAQR6 is linked to a poor prognosis for KIRC patients. Functional enrichment analysis demonstrated that PAQR6 is primarily involved in angiogenesis and pluripotent stem cell differentiation, which are crucial in mediating the development of KIRC. Additionally, we established a ceRNA network that is directly related to overall prognosis, further supporting the role of PAQR6 as a prognostic biomarker for KIRC.ConclusionUsing both computational and experimental methods, this study leads the charge in discovering and verifying PAQR6 as a prognostic biomarker and possible therapeutic target for KIRC. In the future, to determine its molecular mechanism in KIRC carcinogenesis, more in vivo research will be carried out.